Antagonism and narcissism as a conditional relationship: The role of social-engagement traits. (May 2022) - Hart, William; Breeden, Christopher J.; Kinrade, Charlotte; Lambert, Joshua
Abstract: One structural claim of narcissism states that antagonism is a common correlate of grandiose and vulnerable narcissism. However, relations between antagonism and narcissism constructs may depend on other dispositional features within people. For example, some theorizing suggests that antagonism might relate more positively to grandiose narcissism with increments in "boldness" constructs and more positively to vulnerable narcissism with increments in (emotional) "reactivity" constructs. In two studies, Mturk and college-student participants (total N  = 989) completed self-report measures of antagonism constructs (e.g., agreeableness/antagonism), grandiose narcissism, vulnerable narcissism, boldness constructs (e.g., extraversion), and reactivity constructs (e.g., neuroticism). We found no evidence that antagonism related more positively to grandiose narcissism with elevations in boldness constructs or related more positively to vulnerable narcissism with elevations in reactivity constructs. However, we did find that antagonism related more positively to vulnerable narcissism at higher extraversion or lower detachment. The findings supported the idea that relations between antagonism and narcissism may depend on some other dispositional features within people; broadly, this highlights the potential value of considering contingency statements in structural claims about narcissism. Highlights: Mapping the structure of narcissism is a top priority. One structural postulate has vulnerable and grandiose narcissism uniting on antagonism. Some theory anticipates dynamic relations between narcissism forms and antagonism. In the present work, antagonism relates more strongly to vulnerable narcissism at higher social engagement traits. For precision, structural models may be fitted with contingency statements.